The Impact of Digital Technologies on Educational Perfomance (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, in order to further develop the education system and increase the quality of education in Uzbekistan, suggestions are given on the digitization of the education system, the use of modern information technologies in educational processes, and the improvement of its efficiency.